A Strategy for Efficient Preparation of Genus-Specific Diagnostic Antibodies for Snakebites - Long, Chengbo; Wu, Feilong; Lu, Qiumin; Xie, Bing; Shen, Chuanbin; Li, Jiayao; Deng, Yanling; Liang, Ping; Yu, Yongzhi; Lai, Ren (Frontiers in Immunology, 2021)
As said by former United Nations secretary general Kofi Annan, ‘Snakebite is the most important tropical disease you’ve never heard of’. Listed as a priority neglected tropical disease by the World Health Organization, snakebite envenoming (SBE) kills in excess of 125,000 people per year. However, due to the complexity and overlap of snake venom compositions, few reliable venom diagnostic methods for genus-/species-specific identification, which is crucial for successful SBE therapy, are available. Here, we develop a strategy to select and prepare genus-specific snake venom antibodies, which allows rapid and efficient clinical diagnosis of snakebite. Multi-omics approaches are used to choose candidate antigens from snake venoms and identify genus-specific antigenic epitope peptide fragments (GSAEPs) with ideal immunogenicity, specificity, and spatial accessibility. Double-antibody sandwich ELISA kit was established by matching polyclonal antibody against the natural antigen and monoclonal antibody that was prepared by natural protein as antigen, and can specifically target the GSAEPs. The kits shows ability to accurately identify venoms from the similar genera of Trimeresurus and Protobothrops with a detection limit of 6.25 ng/ml on the snake venoms and little cross reaction, thus proving high feasibility and applicability.